Some Aspects of Debates on Curriculum in 19th century South Africa and India - Vikash Kumar Singh (Voices of Teachers and Teacher Educators, 2025)
This paper examines within a comparative manner of four aspects of curriculum in colonial South Africa and India. These are the space of religious versus secular; vocational studies; segregated versus common curriculum; and gender aspects of education. The findings of the study showed that notwithstanding the presence of the same British rule in both countries, differences were present, which were largely caused by the differential social conditions. At the same time, it was not a picture of complete difference, because on certain issues, curriculum in both countries exhibited similar orientation.Curricular knowledge had a very fractured and paradoxical character and this character had developed under very asymmetrical power relationship between the colonial state, the Christian missionaries and the indigenous and western intelligentsia. It was shaped by the reluctant attitude of colonial state to disseminate liberal, secular, rational value of enlightenment. On the other hand it was also shaped by intelligentsia both indigenous and western and the Christian missionaries who had their own agenda in the production and re-production of this curricular knowledge. Colonial curricular knowledge also portrayed the influence of religious revivalism of late 19th century.